Thaalisapaththiri Chooranam (Poly Herbal Formulation) in Siddha Medicine - A literature review - Mufaza, M.; Nisra, H.; Kalaichelvi, S.; Vinotha, S. (International Journal of Ayurvedic Medicine, 2020)
Thaalisapaththiri chooranam (T.C) is a poly herbal formulation and used to treat a wide variety of respiratory tract conditions such as kaasam, shayam, eilai and pitha diseases in Siddha Medicine. It has different ingredients which are having a wide range of therapeutic uses. Although the method of preparation of the T.C is mentioned in the eight text books, same variety of ingredients (eighteen) is mentioned in only two books. Therefore, the preliminary step was to develop the documentary evidences for the medicinal ingredients those are using to prepare the T.C. Data for the review on 18 ingredients from 13 families were collected from relevant text books and research sources from October to December 2019. The characteristics of the ingredients that were identified for the review were morphology; native; parts used; siddha properties such as taste, potency and efficacy; pharmacological actions and phytochemicals. Among these ingredients, all were identified as herbal materials and 2(11.1%) of the species were found in Umbelliferae, Myristicaceae, Piperaceae, Combretaceae and Compositae families. Based on the morphology 8(44.44%) and 6(33.33%) plants were trees and herbs respectively; 8 species (44%) were used as dry fruits. Among these ingredients, 11(39.2%) were pungent in taste, 15(83.3%) hot potency and 12(66%) pungent efficacy. Based on pharmacological actions such as carminative [12(27%)] and stimulant [11(23%)]; phytochemicals such as volatile oil 8(23%) were found in these ingredients. Although this review provides useful documentary evidences for T.C in health management further extensive scientific studies should be carried out to justify in future.
Keywords: Poly herbal formulation; Ingredients; Preparation; Review; Siddha medicine; Thaalisapaththiri chooranam